A longitudinal assessment of acute cough. - Lee, K; Matos, S; Evans, D; White, P; Pavord, I; Birring, S (2013)
RATIONALE: Cough can be assessed with visual analog scales (VAS), health status measures, and 24-hour cough frequency monitors (CF(24)). Evidence for their measurement properties in acute cough caused by upper respiratory tract infection (URTI) and longitudinal data is limited. OBJECTIVES: To assess cough longitudinally in URTI with subjective and objective outcome measures and determine sample size for future studies. METHODS: Thirty-three previously healthy subjects with URTI completed cough VAS, Leicester Cough Questionnaire (LCQ-acute), and CF(24) monitoring (Leicester Cough Monitor) on three occasions, 4 days apart. Changes in subjects' condition were assessed with a global rating of change questionnaire. The potential for baseline first-hour cough frequency (CF(1)), VAS, and LCQ to identify low CF(24) was assessed. MEASUREMENTS AND MAIN RESULTS: Mean ± SD duration of cough at visit 1 was 4.1 ± 2.5 days. Geometric mean ± log SD baseline CF(24) and median (interquartile range) cough bouts were high (14.9 ± 0.4 coughs/h and 85 [39-195] bouts/24 h). Health status was severely impaired. There was a significant reduction in CF(24) and VAS, and improvement in LCQ, from visits 1-3. At visit 3, CF(24) remained above normal limits in 52% of subjects. The smallest changes in CF(24), LCQ, and VAS that subjects perceived important were 54%, 2- and 17-mm change from baseline, respectively. The sample sizes required for parallel group studies to detect these changes are 27, 51, and 25 subjects per group, respectively. CF(1) (<20.5 coughs/h) was predictive of low CF(24). CONCLUSIONS: CF(24), VAS, and LCQ are responsive outcome tools for the assessment of acute cough. The smallest change in cough frequency perceived important by subjects is 54%. The sample sizes required for future studies are modest and achievable.